O efeito do gasto público em saneamento básico na redução dos casos de dengue e diarreia aguda em municípios cearenses: período 2003 a 2012 - Vieira, Antonio Márcio Alves (2017)
The present study aimed to analyze the effects of public expenditures on Basic Sanitation performed by the municipalities of the State of Ceará, for the reduction of diagnosed cases of dengue, and of acute diarrhea in children under two years of age, from 2003 to 2003 2012. The methodology used in this work consisted in the elaboration and estimation of two econometric models with the use of panel data. The main variable of interest of the models was the public expenditure in Basic Sanitation, which lapsed in one year. Waterborne or transmitted diseases such as dengue, acute diarrhea, leptospirosis, among others, are in places where the public services of treated water, garbage collection and sanitary sewage are precarious, the ideal conditions for the emergence and proliferation of these pathologies A contaminated environment has one of its greatest effects being the increase of social risk for the population, especially for the most vulnerable segments, such as children and the elderly, living in less favored areas in urban health infrastructure. It was observed through the study that, on average, the expenditures with Basic Sanitation increased in the set of 184 municipalities of Ceará, during the years surveyed. However, the existence of a greater expenditure with this public service did not necessarily mean a reduction in the number of diagnosed cases of dengue fever recorded in the state of Ceará. Regarding the cases of children under two years of age diagnosed with acute diarrhea, although the estimation of the econometric model did not show statistical significance of the expenditures with Basic Sanitation, a joint analysis of the data allowed us to verify that the number of cases diagnosed for said pathology decreased over the years, a fact that can be explained by the increase in GDP, occurring in all the cities surveyed.